Prosedur Pemberian dan Pengawasan Kredit pada PT Bank Rakyat Indonesia (Persero) Tbk KCP Unit Ambarita - Sidabutar, Irma; Tambunan, Bonafisius; Siahaan, Audrey (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2024)
This study focuses on the procedure for providing and supervising credit, namely People's Business Credit (KUR) and Rural General Credit (KUPEDES), which aims to determine how the procedure for providing and supervising credit is at PT Bank Rakyat Indonesia (Persero) Tbk Ambarita Unit Branch Office. The research method used in this study is descriptive. The results show that the provision of KUR and KUPEDES and their supervision at PT Bank Rakyat Indonesia (Persero) Tbk Ambarita Unit Branch Office has yet to be fully carried out effectively. In credit supervision, it is also expected that the Mantri (account officer) related to the credit section is expected to monitor their customers more often by the applicable credit provision principles to avoid errors that result in bad credit, and supervision should be carried out as often as possible so that credit payments are by the agreement.